Incorporation of Ge in Cu2ZnSnS4 thin film in a Zn-poor composition range. (January 2019) - Lim, Kwang-Soo; Yu, Seong-Man; Seo, Seongrok; Shin, Hyunjung; Oh, Tae-Sik; Yoo, Ji-Beom
Abstract: High conversion efficiency of Cu2 ZnSnS4 (CZTS) thin films have been derived with Cu-poor and Zn-rich compositions, due to detrimental intrinsic defects like SnZn and 2CuZn + SnZn in the stoichiometric compositions. However, the Zn-rich composition results in the formation of a ZnS secondary phase. The trade-off relationship of the detrimental defects and a ZnS secondary phase limit improvement of the CZTS solar cell device. In this study, we found that the performance of a Cu2 Zn(Sn1-x Gex )S4 (CZTGS) device was improved in the Zn-poor composition rather than the Zn-rich composition, because the influence of the detrimental defects (SnZn and 2CuZn + SnZn ) in the Zn-poor composition was significantly reduced by Ge-substitution on the Sn site. Decreasing the Zn composition reduced the formation of the ZnS secondary phase at the interface of the absorber and Mo-back contact. The red-shift of PL emission energy from the band gap energy for CZTGS films was less than that in the CZTS films, indicating the reduction of detrimental defects in the absorber layer. The trade-off between the formation of the ZnS secondary phase and the defects contributed to the change resulting in the optimized Zn composition for improved device performance. Consequently, the CZTS device achieved an optimized efficiency (2.81%) at Zn/Sn = 1.18 (Zn-rich), while the CZTGS device achieved the improved efficiency (4.48%) at Zn/(Sn + Ge) = 0.95. Highlights: Cu2 ZnSnS4 and Cu2 Zn(Sn1-x, Gex)S4 thin films were compared with the various Zn composition. Intrinsic defects were studied to compensation by Ge-substitution in Cu2 ZnSnS4 thin film. PL red-shifting from the band gap was prevented by Ge-substitution on the Sn site. Cu2 Zn(Sn1-x, Gex )S4 solar cell efficiency was more improved in the Zn-poor composition than the Zn-rich composition.